2001
DOI: 10.1128/mmbr.65.1.44-79.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Extremely Radiation-Resistant Bacterium Deinococcus radiodurans Viewed from the Perspective of Comparative Genomics

Abstract: The bacterium Deinococcus radiodurans shows remarkable resistance to a range of damage caused by ionizing radiation, desiccation, UV radiation, oxidizing agents, and electrophilic mutagens. D. radiodurans is best known for its extreme resistance to ionizing radiation; not only can it grow continuously in the presence of chronic radiation (6 kilorads/h), but also it can survive acute exposures to gamma radiation exceeding 1,500 kilorads without dying or undergoing induced mutation. These characteristics were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
612
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 646 publications
(656 citation statements)
references
References 224 publications
18
612
2
3
Order By: Relevance
“…CrtC-type carotenoid 1,2-hydratases have been found in photosynthetic bacteria (Armstrong et al, 1989;Frigaard et al, 2004;Kovács et al, 2003;Ouchane et al, 1997), primarily involved in the biosynthesis of spirilloxanthin, spheroidene, chlorobactene and its derivatives. However, no homologue of the CrtC-type carotenoid 1,2-hydratase has been detected in the D. radiodurans genome (Makarova et al, 2001;White et al, 1999). We identified the gene candidates of carotenoid 1,2-hydratase, dr0091 and dgeo2309, predicted in the gene neighbourhood of crtO from D. radiodurans R1 and D. geothermalis DSM 11300, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…CrtC-type carotenoid 1,2-hydratases have been found in photosynthetic bacteria (Armstrong et al, 1989;Frigaard et al, 2004;Kovács et al, 2003;Ouchane et al, 1997), primarily involved in the biosynthesis of spirilloxanthin, spheroidene, chlorobactene and its derivatives. However, no homologue of the CrtC-type carotenoid 1,2-hydratase has been detected in the D. radiodurans genome (Makarova et al, 2001;White et al, 1999). We identified the gene candidates of carotenoid 1,2-hydratase, dr0091 and dgeo2309, predicted in the gene neighbourhood of crtO from D. radiodurans R1 and D. geothermalis DSM 11300, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…On the basis of this finding we suggested that the co-protease activity rather than the recombination activity of RecA contributed to the extraordinary radiation resistance of D. radiodurans (Satoh et al, 2002). Bioinformatic analysis of the D. radiodurans genome sequence showed that the genome encodes a second, diverged copy of LexA1, LexA2 (DRA0074), which retains the same arrangement of the helix-turn-helix DNA-binding domain and the autocleavage domain (Makarova et al, 2001). Sheng et al (2004) suggested that the product of gene dra0074 is involved in metabolic pathways other than the DNA repair response elicited by irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It can survive doses of radiation that do not exist naturally on Earth. Therefore, it is likely that this radiation tolerance is related to the bacterial response to natural non-radioactive DNA-damaging conditions such as desiccation (Makarova et al, 2001). At the time of writing, eight recognized species belong to the genus Deinococcus (Ferreira et al, 1997;Rainey et al, 1997;Suresh et al, 2004).…”
mentioning
confidence: 99%